PENELUSURAN FLYPAPER EFFECT PADA BELANJA OPERASI DAN BELANJA MODAL PEMERINTAH KOTA DI INDONESIA PERIODE 2010-2012 - Endah Purbarini, 12.42.02.0038; Masdjojo, Gregorius N (Jurnal Mahasiswa Pasca Sarjana, 2014)
This research aims to analyze the possibility of flypaper effect on Operating Expenditure (OE) and Capital Expenditure (CE) of the City Government in Indonesia. The research also tested the effect of the Original Regional Revenue (ORR) and the General Allocation Fund (GAF) against OE and CE  in the period Of 2010-2012. The data used is the realization of the City Governments Budget Report, which provided the sample, which was published through the website www.djpk.depkeu.go.id. The sampling method used is a purposive sampling method with the total sample 56 City Government in Indonesia.  Types of data used are secondary data is data panel (pooling of data) as it is an aggregation of data time series and cross section. Then data analysis use  panel data regression which is estimated by  Fixed Effect Model (FEM) and Random Effect Model (REM). The selection model based on  Hausman testing criteria. Then the research has to use REM estimation. The results of this research indicate that the ORR and GAF have  positive and  significant effect on OE. Furthermore this research find that flypaper effect occurs in OE.  It shows that the impact of GAF  change to the OE change is more than 1% . It is significant. But the GAF is not significant to the CE. The ORR have a positive and significant effect on CE. Furthermore this research find that flypaper effect does not occur on CE. Key words :  The General Allocation Fund (GAF), The Original Regional Revenue (ORR), Operating Expenditure (OE), Capital Expenditure (CE), Flypaper Effect.